2006
DOI: 10.14494/jnrs2000.7.2_29
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Bromide and Iodide Ion-Isotopic Exchange Reactions Using Strongly Basic Anion Exchange Resin Duolite A-113

Abstract: Kinetics of ion-isotopic exchange reaction was studied using industrial grade ion exchange resin Duolite A-113. The radioactive isotopes I and Br were used to trace the ion-isotopic exchange reaction. The experiments were performed in the temperature range of 26.0•Ž to 43.0•Ž and the concentration of external ionic solution varying from 0.005 M to 0.100 M. For bromide ion-isotopic exchange reaction, the calculated values of specific reaction rate, initial rate of bromide ion exchange, and amount of bromide ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…Preliminary studies show that the above exchange reactions are of first order [14][15][16][17][18]. Therefore logarithm of activity when plotted against time gives a composite curve in which the activity initially decreases sharply and thereafter very slowly giving nearly straight line (Figure 1), evidently rapid and slow ion-isotopic exchange reactions were occurring simultaneously [14][15][16][17][18]. Now the straight line was extrapolated back to zero time.…”
Section: Comparative Study Of Ion-isotopic Exchange Reactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Preliminary studies show that the above exchange reactions are of first order [14][15][16][17][18]. Therefore logarithm of activity when plotted against time gives a composite curve in which the activity initially decreases sharply and thereafter very slowly giving nearly straight line (Figure 1), evidently rapid and slow ion-isotopic exchange reactions were occurring simultaneously [14][15][16][17][18]. Now the straight line was extrapolated back to zero time.…”
Section: Comparative Study Of Ion-isotopic Exchange Reactionsmentioning
confidence: 98%
“…The activity of solution was measured at a fixed interval of every 2.0 min. The final activity (A f ) of the solution was also measured after 3h which was sufficient time to attain the equilibrium [14][15][16][17][18]23,24]. The activity measured at various time intervals was corrected for background counts.…”
Section: Study On Kinetics Of Iodide Ion-isotopic Exchange Reactionmentioning
confidence: 99%
“…Fro m the results, it appears that iodide ions exchange at the faster rate as co mpared to that of bro mide ions which was related to the extent of solvation (Tables 3 and 4). [30] in the study of chloride distribution coefficient on strongly basic anion exchange resin observed that the selectivity coefficient between halide ions increased at higher electro lyte concentrations. Adachi et al [31] observed that the swelling pressure of the resin decreased at higher solute concentrations resulting in larger K d values.…”
Section: Comparati Ve Study Of Ion-isotopic Exchange Reactionsmentioning
confidence: 99%
“…The activity of solution was measured at a fixed interval of every 2.0 min. The final activity (A f ) of the solution was also measured after 3 h which was sufficient time to attain the equilibrium (Singare et al 2012;Lokhande et al 2007;Lokhande et al 2008a;Lokhande and Singare 2008;Lokhande et al 2006). The activity measured at various time intervals was corrected for background counts.…”
Section: Study On Kinetics Of Iodide Ion-isotopic Exchange Reactionmentioning
confidence: 99%